Long-term health consequences among individuals with SARS-CoV-2 infection compared to individuals without infection: results of the population-based cohort study CoMoLo Follow-up - Christin Heidemann; Giselle Sarganas; Yong Du; Beate Gaertner; Christina Poethko-Müller; Caroline Cohrdes; Sein Schmidt; Martin Schlaud; Christa Scheidt-Nave (BMC, 2023)
Abstract Background Most of the previous studies on health sequelae of COVID-19 are uncontrolled cohorts and include a relatively short follow-up. This population-based multi-center cohort study examined health consequences among individuals about 1 to 1.5 years after SARS-CoV-2 infection compared with non-infected. Methods The study population consisted of adults (≥ 18 years) from four municipalities particularly affected by the COVID-19 pandemic in the year 2020 who completed a detailed follow-up questionnaire on health-related topics. Exposure was the SARS-CoV-2 infection status (based on IgG antibodies, PCR test, or physician-diagnosis of COVID-19) at baseline (May to December 2020). Outcomes assessed at follow-up (October 2021 to January 2022; mean: 452 days) included recurrent or persistent health complaints, incident diseases, health-related quality of life (PROMIS-29), subjective health, and subjective memory impairment. Logistic and linear regression models were adjusted for baseline sociodemographic and lifestyle characteristics (age, sex, municipality, education, smoking, body mass index), pre-existing health conditions (chronic disease/health problem, health-related activity limitation, depressive/anxiety disorder), and follow-up time. Results Among 4817 participants, 350 had a SARS-CoV-2 infection at baseline and 4467 had no infection at baseline or during follow-up. Those with an infection statistically significantly more often reported 7 out of 18 recurrent or persistent health complaints at follow-up: smell/taste disorders (12.8% vs. 3.4%, OR 4.11), shortness of breath (23.0% vs. 9.5%, 3.46), pain when breathing (4.7% vs. 1.9%, 2.36), fatigue (36.9% vs. 26.1%, 1.76), weakness in legs (12.8% vs. 7.8%, 1.93), myalgia/joint pain (21.9% vs. 15.1%, 1.53) and cough (30.8% vs. 24.8%, 1.34) and 3 out of 6 groups of incident diseases: liver/kidney (2.7% vs. 0.9%, 3.70), lung (3.2% vs. 1.1%, 3.50) and cardiovascular/metabolic (6.5% vs. 4.0%, 1.68) diseases. Those with an infection were significantly more likely to report poor subjective health (19.3% vs. 13.0%, 1.91), memory impairment (25.7% vs. 14.3%, 2.27), and worse mean scores on fatigue and physical function domains of PROMIS-29 than non-infected. Conclusion Even after more than one year, individuals with SARS-CoV-2 infection showed an increased risk of various health complaints, functional limitations, and worse subjective well-being, pointing toward profound health consequences of SARS-CoV-2 infection relevant for public health.